Increased effective reflection and transmission at the GaN-sapphire interface of LEDs grown on patterned sapphire substrates - 吴冬雪 马平 刘波亭 张烁 王军喜 李晋闽 (Journal of semiconductors, 2016)
The effect of patterned sapphire substrate(PSS) on the top-surface(P-Ga N-surface) and the bottomsurface(sapphire-surface) of the light output power(LOP) of Ga N-based LEDs was investigated, in order to study the changes in reflection and transmission of the Ga N-sapphire interface. Experimental research and computer simulations were combined to reveal a great enhancement in LOP from either the top or bottom surface of Ga N-based LEDs, which are prepared on patterned sapphire substrates(PSS-LEDs). Furthermore, the results were compared to those of the conventional LEDs prepared on the planar sapphire substrates(CSS-LEDs). A detailed theoretical analysis was also presented to further support the explanation for the increase in both the effective reflection and transmission of PSS-Ga N interface layers and to explain the causes of increased LOP values. Moreover, the bottom-surface of the PSS-LED chip shows slightly increased light output performance when compared to that of the top-surface. Therefore, the light extraction efficiency(LEE) can be further enhanced by integrating the method of PSS and flip-chip structure design.